Akulturasi Budaya Pernikahan Antara Masyarakat Batak dengan Masyarakat Jawa di Kecamatan Barumun Selatan - Nur Anisah Hasibuan; Erasiah, Erasiah; Hakim, Lukmanul (Universitas Pahlawan Tuanku Tambusai, 2024)
This writing aims to analyse and reconstruct history, looking at the cultural acculturation of marriage between the Mandailing Batak Community and the Javanese Community in South Barumun. In reviewing this research, the author uses a historical research method consisting of four steps, namely heuristics, source criticism, synthesis, and historiography. The results obtained explain that the majority of the population in South Barumun Sub-district are Mandailing Batak people. However, there are also migrants from Java Island. At the beginning of the arrival of the Javanese to South Barumun, they intended to manage the land in the area for farming. The king of Luhat Batang Bulu, Tongku Mangaraja Ronggur Hasibuan, gave the Javanese migrants land to manage and settle on for free. Over time, the marriage between the Javanese and Mandailing Batak communities had a very positive impact, creating a mutual cultural relationship between the two. This can be seen in the cultural arts used in this area, where cultural forms from both ethnicities are still equally maintained. The art of Kuda Kepang, for example, is still preserved today and is often held during weddings and on certain holidays. In addition, the system of inheritance of tribes or clans for descendants of marriages between ethnic Batak and ethnic Javanese in South Barumun is unique.